(3GdcdjGJs - (3eMeO Hf CMeO Hf eMeO Hf QTO GdbQWHj GdCfOdSj, CHh GdhdjO (B((3GdMajO(B)(3,J (B595 (3g` s ((3eMeO Hf eMeO Hf CMeO Hf YHOGdedc s)
(3ChdgG (B:s
(3eHJhQ GdChd hChd eGajg (B: (3Ef GdUfGFY HYVgG GdYde GdWHjYj, hHYVgG Yedj, hgPg efgG UfGYI GdWH, hefgG UfGYI GdJTQjM , CeG GdYde GdWHjYi aEfg s
(3BNQgG (B:s
(3hHGdLedI ef jMVQ dg eG cJHfGg ef GdCbGhjd GdcdjI Cecf Cf jba Ydi GdUhGH hGdNWC ef eOGhGI CUMGH GdcfGfjT aj JaSjQ GdYdGL hGdJQcjH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B318 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B313s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B208 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B257 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs